Editorial (Revista Brasileira Multidisciplinar, 2011)
In this editorial the journal Uniara, we're bringing some reflections on the issues involved in the consolidation of a multidisciplinary character of publication. As discussed earlier, the creation of a multidisciplinary magazine of the University Center of Araraquara intended, in that context, encourage the dissemination of research results and extension produced by its faculty and students. The very transformations and academic evolution of the institution demanded and were reflected in the changes implemented in magazine publishing in form, content, criteria adopted for publication and visibility, enabling an improvement in the scientific quality of the journal. In this process, the journal maintained its multidisciplinary nature, which required the development of a peer database of different areas of expertise to meet the specificities of the articles submitted. The organization of this select group depends not only on knowledge to academic evaluation of manuscripts, such as commitment, always voluntary, the referees with the rules and dates indicated by the editors. This difficulty is being overcome little by little, being necessary to point out what is the contribution of these researchers that has been promoting the development of the quality of this journal. An analysis of articles published in four numbers after the magazine's restructuring process, using as criteria the six areas of categories, namely, communication, rural communities, law, education, business, environment and health, shows a predominance of the theme environment , investigated in several respects, followed by education and health. The diversity of research in the environmental area has shown and reaffirming that the studies on this topic can and are being approached from an interdisciplinary point of view, and are already reflected in environmental preservation actions. This same multi-interdisciplinary approach will be the basis for discussions during the UN Conference on Sustainable Development (Rio + 20), on topics such as green economy, sustainable development, education and poverty eradication, issues that have been published by magazine. For example, in this issue the articles address environmental issues such as health risks by pesticides and environmental awareness for green areas.